2009
DOI: 10.1016/j.earlhumdev.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD47 expression during spontaneous apoptosis targets neutrophils for phagocytosis by monocyte-derived macrophages

Abstract: Background-Neutrophils (PMN) are the primary leukocyte responders during acute inflammation. After migrating into the tissues, PMN undergo programmed cell death (apoptosis) and are subsequently removed via phagocytosis by resident macrophages during the resolution phase. Efficient phagocytosis of apoptotic neutrophils is necessary for successful resolution. CD47 plays a critical role in mediating the phagocytic response, although its role in the phagocytosis of apoptotic PMN in incompletely understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…To test this possibility, we analyzed changes in apoptotic death in neutrophils from human and murine origin, with the finding that the presence of this metalloprotease triggered an increment in their apoptosis. In this regard, previous works have described the ability of proteins containing thrombospondin type-1 repeats to interact with surface proteins such as CD36 and CD47 (30,31), that can modulate neutrophil death and clearance (32,33). Hence, it is conceivable a model in which ADAMTS-12 could participate in similar protein interactions through its thrombospondin domains.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we analyzed changes in apoptotic death in neutrophils from human and murine origin, with the finding that the presence of this metalloprotease triggered an increment in their apoptosis. In this regard, previous works have described the ability of proteins containing thrombospondin type-1 repeats to interact with surface proteins such as CD36 and CD47 (30,31), that can modulate neutrophil death and clearance (32,33). Hence, it is conceivable a model in which ADAMTS-12 could participate in similar protein interactions through its thrombospondin domains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a blocking monoclonal anti-CD47 antibody enhances phagocytosis of apoptotic neutrophils (28, 29). Interestingly, in our mouse toxicity studies, administration of a blocking anti-mouse CD47 antibody led to selective depletion of neutrophils, while other hematopoietic cells were unaffected (6).…”
Section: Discussionmentioning
confidence: 99%
“…In our original study (de Almeida et al, 2005), we had reported hyperphagocytosis of peritoneal macrophages from the B10.129Ola strain used in the current study, as compared with wild type C57BL/10SnJ, but wild type B10.129Ola macrophages were not examined. The CD47-Sirpa signaling system, however, also regulates properties of polymorphonuclear cells, such as adhesion, migration and phagocytosis, as well as macrophage-mediated clearance of apoptotic neutrophils, with robust functional consequences (Parkos et al, 1996;Liu et al, 2001;Lawrence et al, 2009;Myers et al, 2011;Zen et al, 2013;Stenberg et al, 2013Stenberg et al, , 2014Greenlee-Wacker et al, 2014). Interestingly, we have found no difference between Prnp-null and wild type neutrophils taken from B10.129Ola mice in their sensitivity to spontaneous or peroxideinduced apoptosis in vitro (Mariante et al, 2012), nor in their recruitment to the peritoneal cavity following in vivo injections of zymosan (R.M.…”
Section: Discussionmentioning
confidence: 99%